On instability of the equilibrium state of nonholonomic systems - Sosnitskii, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish a criterion of instability for the equilibrium state of nonholonomic systems, in which gyroscopic forces may dominate over potential forces. We show that, similarly to the case of holonomic systems, the evident domination of gyroscopic forces over potential ones is not sufficient to ensure the equilibrium stability of nonholonomic systems.